Short-term performance of implant-supported restorations fitted in general dental practice: a retrospective study - Klotz, Anna-Luisa; Krisam, Johannes; Seyidaliyeva, Aida; Rammelsberg, Peter; Zenthöfer, Andreas (The international journal of oral & maxillofacial implants, 2019)
Anna-Luisa Klotz, DMD/Larissa Ott, DDS/Johannes Krisam, PhD/Stephanie Schmitz, DMD/Aida Seyidaliyeva/Peter Rammelsberg, DMD, PhD/Andreas Zenthöfer, DMD: Purpose: The purpose of this retrospective clinical study was to evaluate the short-term performance of - implants and implant-supported dental restorations (single crowns, fixed/removable dental prostheses, - and overdentures) and to identify risk factors for prosthetic complications under the conditions of general - dental practice. Materials and Methods: De-identified data extracted from electronic patient records were - analyzed to clarify the research question. Patient-related variables and implant- and suprastructure-related - variables were documented for each patient. The probability of complication-free survival after 1 and 2 - years was evaluated using the Kaplan-Meier method. In addition, the prosthetic complications were analyzed - using Cox regression models. Results: Eighty-four patients with 134 healed dental implants supporting 107 - restorations were studied over a clinical period of up to 52 months (mean: 23.9 months). Of all implants - placed (n = 186), nine (4.8%) failed during the healing phase. Of the healed implants, peri-implant bone - loss occurred for two implants among two patients. Nonetheless, these two implants remained functional. - Complications were as follows: peri-implantitis (1.5%), loss of retention (10%), loosening of the abutment - screw (6%), and chipping of the veneer material (3.7%). The probability of complication-free survival for - suprastructures alone was 92% (95% CI: 86% to 96%) after 1 year and 84% (95% CI: 75% to 90%) after 2 - years of clinical service. Taking into consideration all complications/failures of implants and of restorations, - complication-free survival was 86% (80% to 91%) and 79% (70% to 85%) after 1 and 2 years, respectively. - Conclusion: Both healed dental implants and implant-supported restorations placed in general practice - present high survival; the survival rates seen during the quite short observation period appear comparable - to institutional study outcomes. However, technical prosthetic complications are not uncommon among - restorations in general dental practice and probably occur more often than reported from university studies.
Gesehen am 03.12.2019